Monitoring of residential drinking water service consumption using Human Machine Interaction (HCI) techniques - Chilcañan Capelo, David Andrés (2019)
The integration of the drinking water network with information and communication technologies (ICTs) is the future of automated metering for users and service providers, the modern world cannot be conceived without water and the current infrastructure of manual metering, is poorly adapted to current needs, every day the demand for this vital liquid is greater and data collection from meters must be automated, allowing users to make queries of water consumption and tariffs to pay, however, it is necessary to create a centralized intelligent network with better adaptability to the meter; Implementing these technologies is expected to significantly reduce reading times in measurements, failure reports and changes in the drinking water network. In developing countries such as Ecuador, does not provide a metering infrastructure, however in the country, is thinking about creating Smart Grids for the adequacy of intelligent cities, a big step into the future. This article presents an implementation proposal for Smart Water Meter (SWM), by means of a virtual assistant and a metering network, allowing to consult the m3 of water consumed per day, week and month, as well as the total amount to be paid per consumption, integrating hardware and free software, for greater security in communications.